Mitigating drought-associated reproductive failure in maize: From physiological mechanisms to practical solutions - Zhiwei Wang; Yi Yu; Xiang Chen; Yangyang Li; Ashley Jones; Ray J. Rose; Yong-Ling Ruan; Youhong Song (Crop Journal)
Maize serves as a crucial cereal crop globally, yet the escalating frequency of drought stress during the reproductive phase poses a significant threat to grain yield by causing an irreversible loss in kernel number. Enhancing reproductive drought tolerance in maize requires elucidating the physiological mechanisms underlying its response to drought stress, which can then be incorporated into the development of new maize varieties through breeding programs. Additionally, innovative cultivation practices must be devised to complement these genetic improvements. In this review, the timing, duration, and severity of drought stress during the reproductive stage and their effects on maize kernel set are assessed, providing a basis for constructing a framework that links kernel setting to drought stress. Based on this framework, reproductive drought tolerance from tasseling through post-fertilization kernel establishment is subsequently examined. Evidence indicates that drought-induced fertilization failure is primarily due to delayed pollination resulting from slower silk elongation, which is caused by the loss of cell turgor and reduced carbon supply. Meanwhile, kernel abortion after fertilization is mainly triggered by carbohydrate starvation, increased ethylene emission, and the accumulation of abscisic acid (ABA). Therefore, sugar metabolism, hydraulic status, and hormone signaling collectively regulate maize’s kernel setting tolerance to drought stress in a synergistic manner. Several novel gene candidates with potential for conferring drought tolerance in maize have been identified, offering promising targets for genetic improvement through genome editing combined with targeted cultivation practices to enhance maize drought tolerance and ensure stable grain yield in future crops.